Telomeric repeat-containing RNA is dysregulated in acute myeloid leukemia - Catto, Luiz Fernando B.; Zanelatto, Leonardo C.; Donaires, Flavia S.; de Carvalho, Vinicius S.; Santana, Bárbara A.; Pinto, André L.; Fantacini, Daianne; de Souza, Lucas Eduardo B.; Fonseca, Natasha P.; Telho, Bruno S.; Ayrosa Madeira, Maria Isabel; Barbosa Pagnano, Katia Borgia; et al. (Blood advances, 2023)
•TERRA is repressed in primary human hematopoietic cells (in the bone marrow and peripheral blood), regardless of their telomere lengths.•TERRA is dysregulated in a subset of AML characterized by higher R-loop formation and low TERT and RNAseH2 expression. [Display omitted] TERRA (telomeric repeat-containing RNA) is a class of long noncoding RNAs transcribed from subtelomeric and telomeric regions. TERRA binds to the subtelomeric and telomeric DNA–forming R-loops (DNA-RNA hybrids), which are involved in telomere maintenance and telomerase function, but the role of TERRA in human cells is not well characterized. Here, we comprehensively investigated for the first time TERRA expression in primary human hematopoietic cells from an exploratory cohort of patients with acute myeloid leukemia (AML), patients with acute lymphoblastic leukemia (ALL), patients with telomere biology disorder (TBD), and healthy subjects. TERRA expression was repressed in primary human hematopoietic cells, including healthy donors, patients with ALL, and patients with TBD, irrespective of their telomere length, except for AML. A second cohort comprising 88 patients with AML showed that TERRA was overexpressed in an AML subgroup also characterized by higher R-loop formation, low TERT and RNAseH2 expression, and a paucity of somatic splicing factor mutations. Telomere length did not correlate with TERRA expression levels. To assess the role of TERRA R-loops in AML, we induced R-loop depletion by increasing RNAseH1 expression in 2 AML cell lines. Decreased TERRA R-loops in AML cell lines resulted in increased chemosensitivity to cytarabine. Our findings indicate that TERRA is uniformly repressed in primary human hematopoietic cells but abnormally expressed in an AML subset with low telomerase.